PROBATION IN THE REPUBLIC OF KAZAKHSTAN: CURRENT ISSUES AND DEVELOPMENT TRENDS - Rakhimberdin Куат Хажумуханович (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2025)
The article examines a range of systemic, interrelated legal, doctrinal, and practical issues associated with more than a decade of experience in incorporating probation supervision into the criminal legislation of the Republic of Kazakhstan. Attention is given to the concept of probation as a special type of socio-legal and post-criminal control. The author concludes that the Kazakhstani legislature has superficially adopted this scientific understanding and has not pursued the creation of an independent form of probation within criminal law. Instead, probation was made only one of the substantive elements of the punishment in the form of restriction of freedom. The author convincingly and clearly demonstrates that methodological and managerial errors in the implementation of the probation institution in Kazakhstan have led to the emergence of several negative trends, causing probation to diverge from the recommendations of international UN legal instruments and the best practices of global alternatives to imprisonment. These trends, in particular, manifest in the fact that punishment in the form of restriction of freedom has become a primary competitor to not only imprisonment but also to the classical institution of suspended sentencing. The author believes that this creates risks of undermining the practical application of all non-custodial sentences. Criticizing the mistakes and missteps in organizing the national probation system, the author concludes that overcoming them is necessary and outlines the main elements of a factual probation strategy that will allow for truly high results in both its humanity and effectiveness.